2013
DOI: 10.3390/molecules18022052
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Anti-Inflammatory Effect of Chalcone and Chalcone Analogues in a Zebrafish Model

Abstract: The aim of this study was to investigate novel chalcones with potent anti-inflammatory activities in vivo. Chalcone and two chalcone analogues (compound 5 and 9) were evaluated using a caudal fin-wounded transgenic zebrafish line “Tg(mpx:gfp)” to visualize the effect of neutrophil recruitment dynamically. Results showed that treatment with compound 9 not only affected wound-induced neutrophil recruitment, but also affected Mpx enzymatic activity. Moreover, protein expression levels of pro-inflammatory factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 22 publications
0
30
0
4
Order By: Relevance
“…In contrast, excessive or prolonged inflammation may inhibit or delay the bone tissue repair. Thus, the anti-inflammatory property of chalcones as reported by Chen et al 21 may have contributed to the improvement of the bone repair stimulus observed in our study, as in animals treated with chalcones no inflammation signs were observed. Previous studies 16 have shown that a single application of chalcone in rat calvarial defects reduces the critical defect size after 30 days of treatment and promotes complete wound closure after 45 days.…”
mentioning
confidence: 45%
“…In contrast, excessive or prolonged inflammation may inhibit or delay the bone tissue repair. Thus, the anti-inflammatory property of chalcones as reported by Chen et al 21 may have contributed to the improvement of the bone repair stimulus observed in our study, as in animals treated with chalcones no inflammation signs were observed. Previous studies 16 have shown that a single application of chalcone in rat calvarial defects reduces the critical defect size after 30 days of treatment and promotes complete wound closure after 45 days.…”
mentioning
confidence: 45%
“…[28][29][30][31][32] Numerous dietary chalcones and their derivatives have been reported to interfere with inflammatory processes. [33][34][35][36][37] In the present study, we isolated seven compounds 1-7 from the extracts of A. keiskei (Fig. 1A) and evaluated their anti-inflammatory properties through activity-guided procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Senyawa kalkon dilaporkan memiliki bioaktivitas yang menarik sebagai antioksidan (Oktavani et al, 2014), antikanker (Brahmana et al, 2013), anti-inflamasi (Chen et al, 2013), antialzheimer (Pan et al, 2012) dan antimikroba (Eryanti et al, 2010). Bioaktivitas yang terdapat pada senyawa kalkon selain disebabkan oleh adanya gugus α, β tak jenuh yang terdapat pada senyawa kalkon juga dipengaruhi oleh substituen yang terikat pada kedua cincin aromatiknya (Kamble, 2011).…”
Section: Pendahuluanunclassified